5 key strategies lessen regulatory hurdles for international students. Issue 1 (7th February 2022) - Sanford, Amy Aldridge; Raj, Rishi
Abstract : A little more than 1 million students with international student or scholar visas are currently enrolled in institutions of higher education in the United States, making up nearly 6% of all postsecondary enrollment within the country. NAFSA, the world's largest professional association dedicated to international education, reported that in 2019–2020 alone, international students contributed $38.7 billion to the U.S. economy ( read more at  https://bit.ly/3AfNCla ).